Effect of random perturbations on adaptive observation techniques - Hossen, M. J.; Navon, Ionel Michael; Dǎescu, Dacian N. (© 2012 John Wiley & Sons, Ltd., 2016)
his article was published in the International Journal for Numerical Methods in Fluids [© 2011 John Wiley & Sons, Ltd.] and the definite version is available at : http://dx.doi.org/10.1002/fld.2545 The Journal's website is at:http://onlinelibrary.wiley.com/doi/10.1002/fld.2545/abstract